Pertumbuhan, Serapan Hara dan Kualitas Turfgrass pada Beberapa Dosis Pemberian Pupuk Hayati Mikoriza - Guntoro, Dwi; Purwoko, Bambang S. (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The objective of the research was to study the effect of mycorrhiza dosage on nutrient uptake, growth and turfgrass quality.  The research was conducted at IPB turfgrass experimental farm, Darmaga, Bogor.  The experiment was arranged in randomized complete block design with four replications.  The treatment consisted of five dosages of mycorrhiza (100, 200, 300, 400, and 500 g per pot).  The result showed that application of mycorrhiza at 300 g per pot increased coverage area and dry weight of clipping, and decreased vertical height, but it did not significantly increase nutrient uptake and quality of turfgrass compared to control.   Key words :  Mycorrhiza, turfgrass, growth, nutrient uptake, quality